Case Report of Chronic Eosinophilic Leukemia Associated with Long-Term Use of Infliximab - Morse, William; Amin, Harshad; Nawaz, Haroon; Lopez, Cynthia; Sanati, Farhad (Archives of Clinical and Medical Case Reports, 2024)
Hypereosinophilic syndrome (HES) is a rare condition in which the quantity of eosinophils in the body’s blood and tissues increases substantially. Hypereosinophilic syndrome can often go underdiagnosed as the symptoms such as cough, malaise, chills, night sweat, and flulike symptoms can often be attributed to allergic causes. We present a patient who has been diagnosed with Hypereosinophilic syndrome, later determined to be chronic eosinophilic leukemia, after long-term treatment with infliximab for ulcerative colitis. Follow-up immunochemistry showed that discontinuation of infliximab improved the polyclonality of eosinophils in our patient. Further research and reported cases will help us better understand this relationship.